Non-invasive brain stimulation for fibromyalgia: current trends and future perspectives - Zhang, Jia-Hao; Liang, Jian; Yang, Zhong-Wei (Frontiers in Neuroscience, 2023)
Fibromyalgia, a common and enduring pain disorder, ranks as the second most prevalent rheumatic disease after osteoarthritis. Recent years have witnessed successful treatment using non-invasive brain stimulation. Transcranial magnetic stimulation, transcranial direct current stimulation, and electroconvulsion therapy have shown promise in treating chronic pain. This article reviews the literature concerning non-invasive stimulation for fibromyalgia treatment, its mechanisms, and establishes a scientific basis for rehabilitation, and discusses the future directions for research and development prospects of these techniques are discussed.